2014
DOI: 10.1002/app.41172
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and barrier properties of thermoplastic whey protein isolate/ethylene vinyl acetate blends

Abstract: Crude oil is becoming scarcer and more expensive, resulting in alternative biobased or partially biobased materials gaining importance in the field of plastic packaging and encouraging the development of naturally derived, protein-based plastics (Endres, 2009; Jones and McClements, Compreh. Rev. Food Sci. Food Safety 2010, 9, 374; Khwaldia et al., Compreh. Rev. Food Sci. Food Safety 2010, 9, 374). A strategy to improve extrusion processing behavior of proteins is the blending with other polymers. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
(100 reference statements)
1
10
0
Order By: Relevance
“…Moreover, SPI-based probes do not experiment a noticeable decrease in σ max when after adding SB an increase in E takes place. Interestingly, this mechanical response is different to that one previously found by Felix et al [10,19] and Rombouts et al [20] , however are in consonance with the mechanical properties found by Schmid et al [21] and Tummala et al [22] In any case, these elastic responses are consistent with the results from DMTA that showed lower elastic modulus (E') for the system without SB (Figure 2A). These results indicate the feasibility of modulating mechanical properties of bioplastics where mechanical properties obtained after changing the plasticizer used are suitable for different applications.…”
Section: Dynamic Mechanical Temperature Analysis (Dmta)supporting
confidence: 87%
“…Moreover, SPI-based probes do not experiment a noticeable decrease in σ max when after adding SB an increase in E takes place. Interestingly, this mechanical response is different to that one previously found by Felix et al [10,19] and Rombouts et al [20] , however are in consonance with the mechanical properties found by Schmid et al [21] and Tummala et al [22] In any case, these elastic responses are consistent with the results from DMTA that showed lower elastic modulus (E') for the system without SB (Figure 2A). These results indicate the feasibility of modulating mechanical properties of bioplastics where mechanical properties obtained after changing the plasticizer used are suitable for different applications.…”
Section: Dynamic Mechanical Temperature Analysis (Dmta)supporting
confidence: 87%
“…The possibility of better controlling the processing properties of whey protein by blending it with poly(ethylene-co-vinyl acetate) (EVA) was evidenced by Schmid et al [105]. In fact they succeeded in preparing flexible flat die continuously extruded films from plasticized whey protein blended with EVA.…”
Section: Extrusionmentioning
confidence: 99%
“…Several studies have already proven the potential of plant and animal based proteins for their packaging relevant properties [20]. For instance, protein films made from whey protein isolate (WPI) are well studied in terms of edible film and packaging related applications [21][22][23][24][25][26][27]. However, most of the proteins characterized in these studies such as soy, whey, or wheat proteins are suitable for a use in food and feed.…”
Section: International Journal Of Polymer Sciencementioning
confidence: 99%